2010
DOI: 10.1149/1.3299365
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Electrochemical Carboxylation of Polychloromethanes at Zinc Cathode in Acetonitrile

Abstract: An efficient and selective electrochemical carboxylation process of some polychloromethanes was developed to synthesize chloroacetic acids using a zinc cathode and sacrificial anodes under a galvanostatic regime. The electrochemical behavior of carbon tetrachloride ͑CT͒, chloroform ͑CF͒, and its carboxylated products was studied by cyclic voltammetry in acetonitrile using tetrabutylammonium perchlorate as a supporting electrolyte in the presence and absence of CO 2 . Galvanostatic electrolyses of CT and CF in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The electrocarboxylation of organic halides can also be considered as an alternative dechlorination pathway for chlorobenzenes [ 122 ] and polychloromethanes [ 142 ]. While the synthesis of halogenated reagents is rather hazardous, the electrocarboxylation of organic halides is an interesting method to revalue waste products, like for example carbon tetrachloride, a toxic liquid, causing ozone depletion.…”
Section: Reviewmentioning
confidence: 99%
“…The electrocarboxylation of organic halides can also be considered as an alternative dechlorination pathway for chlorobenzenes [ 122 ] and polychloromethanes [ 142 ]. While the synthesis of halogenated reagents is rather hazardous, the electrocarboxylation of organic halides is an interesting method to revalue waste products, like for example carbon tetrachloride, a toxic liquid, causing ozone depletion.…”
Section: Reviewmentioning
confidence: 99%
“…The majority of electrochemical degradation studies on CVOCs have targeted liquid CVOC removal due to groundwater contamination. Two electrocatalytic processes have been devised for this purpose; that is, direct electrocatalytic oxidation (DEO) using an undivided electrolytic cell and boron doped diamond (BDD) and PbO 2 electrodes, which achieved complete mineralization of CVOCs, , and direct electrocatalytic reduction (DER) using a similar undivided electrolytic cell with Ni or Ag cathodes, which achieved good degradation efficiencies for CVOCs present in surface and groundwater aquifers. , Several studies have shown cathodic DER is more favorable for CVOC degradation, and to enhance this process, researchers have utilized a packed bed multiphase iron oxide column, a concentric 3D copper column, and a granular graphite reactor . Furthermore, the DER process has been carried out in several aprotic media, such as, acetonitrile (AN) and dimethylformamide (DMF) and in ethanol/water mixtures using different Zn, Ag, and carbon cathodes to synthesize useful compounds from CCl 4 . ,, On the other hand, it has been proposed that secondary products generated by reduction directly on an electrode’s surface by hydrogen adsorption or water splitting could be utilized to degrade target organic pollutants, considered as indirect reduction processes, as shown below: …”
Section: Introductionmentioning
confidence: 99%
“…21 Furthermore, the DER process has been carried out in several aprotic media, such as, acetonitrile (AN) and dimethylformamide (DMF) and in ethanol/water mixtures using different Zn, Ag, and carbon cathodes to synthesize useful compounds from CCl 4 . 9,10,22 On the other hand, it has been proposed that secondary products generated by reduction directly on an electrode's surface by hydrogen adsorption 23 or water splitting 13 could be utilized to degrade target organic pollutants, considered as indirect reduction processes, as shown below:…”
Section: ■ Introductionmentioning
confidence: 99%